عجز الموازنة العامة للدولة وعلاجه في الاقتصاد الوضعي - لحسن, دردوري (Recherches économiques et managériales; Vol. 14 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE), 2013)
يعتبر موضوع عجز الموازنة العامة للدولة من أهم المواضيع التي يولى لها الاقتصاديين اهتماما كبيرا وذلك لما تمثله الموازنة العامة للدولة من أهمية في الاقتصاد الوطني ،حيث تحاول معظم الدول سواء كانت متقدمة أو نامية الوصول إلى تحقيق التوازن الاقتصادي على جميع الأصعدة ،خصوصا ما تعلق بالتوازن في ميزان المدفوعات والتوازن في الموازنة العامة ،لذلك تسعى هذه الدول جاهدة لتنويع إيراداتها وتنميتها من جهة وترشيد نفقاتها من جهة أخرى ، إلا انه فمن الواضح أن معظم الدول تعاني من مشكل عجز الموازنة العامة ودلك بسبب التزايد الهائل في نفقاتها العامة ومحدودية إيراداتها ،والتي أصبحت لا تستطيع تغطية نفقاتها من جهة ومن جهة أخرى تركز إيراداتها على مصادر محدودة وغير مستقرة ،وذلك ما تعاني منه الدول النامية بوجه التحديد والجزائر بوجه الخصوص .  Abstract: The  deficiency in general balancing is considered as one of the most important state’s issues for the economists because the great important in the national economy since different countries either developed or undeveloped try to realize the economic balance on all scales specially what’s considered with the expenditures balance and in the general balancing that’s why all the countries trying to diversify its incomes in order to get it more developed but its so clear that most of countries suffer from the general balancing problem and this is because of the great raising in their general expenditures and the limitation of its incomes that become unable to cover its expenditures and in the other side its incomes focused on limited unstable resources and the undeveloped countries suffer from specially Algeria